2013
DOI: 10.7202/1015295ar
|View full text |Cite
|
Sign up to set email alerts
|

L’expérience des demandeurs d’asile détenus au Canada

Abstract: Au Canada, les demandeurs d’asile détenus en vertu des lois sur l’immigration sont enfermés dans des établissements de type carcéral, même si moins de 6 % d’entre eux sont soupçonnés de criminalité ou de dangerosité. Nous présentons un survol de la situation canadienne, incluant des données tirées de notre récente étude sur l’impact de la détention sur la santé mentale des demandeurs d’asile. Cette étude fut menée auprès de 122 demandeurs d’asile adultes détenus dans des centres de surveillance de l’immigratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
3
1
1
Order By: Relevance
“…A study of migrants, some of whom had been detained upon arrival in Canada and some of whom were not, with 50% and 65.1%, respectively, from sub-Saharan Africa, reported a PTSD prevalence of 37.7% and 18.2%. 34 These rates are still low compared to the results of the present study. However, a study of urban Indigenous women in Canada showed an even higher prevalence than the present study (83.2%).…”
Section: Discussioncontrasting
confidence: 78%
“…A study of migrants, some of whom had been detained upon arrival in Canada and some of whom were not, with 50% and 65.1%, respectively, from sub-Saharan Africa, reported a PTSD prevalence of 37.7% and 18.2%. 34 These rates are still low compared to the results of the present study. However, a study of urban Indigenous women in Canada showed an even higher prevalence than the present study (83.2%).…”
Section: Discussioncontrasting
confidence: 78%
“…Current pediatric evidence, though limited to the United Kingdom and Australia, consistently demonstrates psychological harm associated with detention (Lorek et al, 2009; Mares & Jureidini, 2004; Mares et al, 2002; Newman & Steel, 2008). There is only one report including case studies on children in Canadian detention centers (Canadian Council for Refugees, 2009), though studies on detained adult asylum seekers describe a deleterious effect on mental health (Cleveland, Dionne-Boivin, & Rousseau, 2013; Cleveland & Rousseau, 2013). The aim of this article is to describe children’s experience of detention in terms of their daily life, routine, social interactions and their emotional and behavioral responses.…”
mentioning
confidence: 99%
“…Past research had found social connectedness to be a key determinant of asylum seekers’ mental health ( 62 ). For example, enduring longer periods awaiting family reunification, not having access to family support or local connections and facing discrimination due to a rise in xenophobia contributes to feelings of loneliness and is associated with higher levels of depression among this population ( 17 , 18 , 63 ). Therefore, psychosocial workshops with the aim of bridging social connection may protect claimants’ mental health through restoration of bonds and networks.…”
Section: Discussionmentioning
confidence: 99%
“…Research has now shown that for asylum seekers these post-migration difficulties were significantly exacerbated by the pandemic, compromising their mental health and increasing risk of suicide ( 16 , 17 ). Asylum seekers’ living and working conditions – as security guards, custodians in hospitals, and personal care attendants in long-term care facilities – deepened their isolation due to shift work and fears of contamination and put them at higher risk of contracting COVID-19 ( 18 , 19 ). Unlike many host-country peers who readily transitioned to online spaces to seek social support, claimants had no straight-forward solution to combat isolation because of lack of access to technology and closure of public spaces ( 2 ).…”
Section: Introductionmentioning
confidence: 99%